2009
DOI: 10.3758/mc.37.6.850
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of word frequency and concreteness in immediate serial recall

Abstract: Word frequency and word concreteness are language attributes that have been shown to independently influence the recall of items in verbal short-term memory (STM). It has been argued that such effects are evidence for the action of long-term memory knowledge on STM traces. However, research to date has not investigated whether these variables interact in serial recall. In two experiments, we examined the behavior of these variables under factorial manipulation and demonstrated that the effect of word frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 50 publications
(172 reference statements)
4
54
1
1
Order By: Relevance
“…The finding of a frequency effect on item memory but not on order memory has been determined using a serial recall task (Poirier & Saint-Aubin, 1996;Miller & Roodenrys, 2009;Morin et al, 2006;Allen & Hulme, 2006). Thus, as previously suggested, an effect of frequency on order information could be masked by differences in item recall.…”
Section: Rationalementioning
confidence: 81%
See 2 more Smart Citations
“…The finding of a frequency effect on item memory but not on order memory has been determined using a serial recall task (Poirier & Saint-Aubin, 1996;Miller & Roodenrys, 2009;Morin et al, 2006;Allen & Hulme, 2006). Thus, as previously suggested, an effect of frequency on order information could be masked by differences in item recall.…”
Section: Rationalementioning
confidence: 81%
“…Further studies have supported this claim with no frequency effect on conditionalised order errors using pure lists (Allen & Hulme, 2006;Morin, Poirier, Fortin, & Hulme, 2006;Miller & Roodenrys, 2009) or mixed lists (Morin et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been proposed that these LTM contributions to immediate memory arise from redintegration processes wherein the partially decayed memory traces are reconstructed by sampling appropriate candidates from LTM (e.g., Hulme et al, 1997;Hulme, Newton, Cowan, Stuart, & Brown, 1999;Nairne, 2002;Schweickert, 1993). Under this view, the short-term phonological record itself is independent of lexical and semantic knowledge: LTM representations support recall only at the moment of retrieval by Bcleaning up^degraded phonological traces in memory through a process that matches partial traces and performs pattern completion (Miller & Roodenrys, 2009). Lexical effects would occur because nonwords, contrary to words, have no matching lexical representations in the language networks.…”
Section: The Temporary Activation Of Long-term Language Representationsmentioning
confidence: 99%
“…Lexical variables refer to "word properties, such as word frequency and concreteness, which reflect differences in the way in which words are represented in long-term or lexical memory" (Stuart & Hulme, 2009, p. 157). Lexical effects include the better recall of high-frequency words over lowfrequency words (the word frequency effect; see, e.g., Hulme, Stuart, Brown, & Morin, 2003;Roodenrys & Quinlan, 2000), of words over nonwords (the lexicality effect; see, e.g., Hulme, Maughan, & Brown, 1991;Multhaup, Balota, & Cowan, 1996), of concrete words over abstract words (the effect of word concreteness or imageability; see, e.g., Miller & Roodenrys, 2009;Walker & Hulme, 1999), and of semantically related words over unrelated words (the effect of semantic similarity; see, e.g., Poirier & Saint-Aubin, 1995;Tse, 2009). Saint-Aubin and Poirier (1999) showed that lexical variables modulate item retention.…”
mentioning
confidence: 99%